ANALISIS PERMINTAAN BERAS ORGANIK DI KOTA SURAKARTA - Fitriah, Dina; Marwanti, Sri; Antriyandarti, Ernoiz (Jurnal Social Economic of Agriculture, 2020)
Research aims to understand variable influence the price of organic rice, the price of nonorganic rice, chicken egg price, education, income, the number of family members, preference on the organic rice in the city of surakarta and elasticity demand. The basic method used in this research is descriptive and analytical method with survey research technique. The method of determining the location of the research is aimed at Surakarta City. The sampling method used is accidental sampling with 100 respondents. Data analysis used the multiple linear regression analysis. This research result indicates the price of organic rice , the price of non-organic rice, the price of chicken egg, education, income, the number of family members, and preference together had an influence on the request of organic rice. The factors that influence individual is organic rice price, non-organic rice price, chicken egg  price, and income. The organic rice price elasticity was negative (-0,683) shows that the organic price is inelastic. The income elasticity was positive (0,611) shows that rice organic included in a category of normal good. Non-organic rice price cross elasticity was positive (1,454) means non-organic rice of substitution to organic rice. Chicken egg price cross elasticity was negative (-1,060) means egg of complementary to organic rice.Keywords: Demand, Elasticity, Organic Rice, Regression